Afroargentinian music through the iconographic documentation (2007)
The purpose of this article is to enrich knowledge onAfroargentinian music through iconographic documentation.In the past, iconographic sources were usedmerely as illustrations and/or as decortive frames thatdid not raise questions or offer answers. The analysis ofvisual sources opens a sui géneris door for the explorationof the past and understanding of the present musicalmanifestations of this group.